A novel biochar supported CMC stabilized nano zero-valent iron composite for hexavalent chromium removal from water. (February 2019) - Zhang, Shuai; Lyu, Honghong; Tang, Jingchun; Song, Benru; Zhen, Meinan; Liu, Xiaomei
Abstract: In this study, novel biochar supported nano-scale zero-valent iron (biochar-CMC-nZVI) stabilized by carboxymethyl cellulose (CMC) was developed and used for the removal of hexavalent chromium (Cr(VI) from aqueous solution. With the stabilization of CMC, nZVI particles (about 80 nm) were effectively dispersed onto the surface of biochar, which inhibited the aggregation of nZVI and resulted in the smaller particle size of nZVI on the surface of biochar. The results showed that the specific surface area of the composite was 11.1 m 2 /g, lower than that of pristine biochar. The basic element composition was C, O, and Fe with a large number of oxygen-containing functional groups (−COOH, OH, and OCO) observed on the surface. Cr(VI) was reduced to Cr(III) by the composite material, mainly due to the reduction of nZVI on the biochar surface. Upon reaction with Cr(VI), Crx Fe1-x (OH)3 and Fex Cry O4 were deposited on the surface of biochar-CMC-nZVI composite. Electrostatic attraction, reduction, and surface complexation were the dominant removal mechanisms. The results showed that the 100 mg/L Cr(VI) could be removed completely by biochar-CMC-nZVI within 18 h, at a dosage of 1.25 g/L and an initial pH of 5.6. Cr(VI) removal by biochar-CMC-nZVI was favored by lower pH. The pseudo-second-order kinetic model and the Langmuir isothermal adsorption model fitted well with the sorption kinetic and isotherm data, indicated Cr(VI) adsorption mechanism was a chemisorption based multi-layer adsorption. The present study demonstrated the promise of biochar-CMC-nZVI composite as a low-cost, "green", and effective sorbent for removal of Cr(VI) in the environment. Graphical abstract: Highlights: CMC supported the development of spherical nZVI on biochar. Biochar-CMC-nZVI composite showed enhanced removal ability of Cr(VI). pH has important effect on the reaction process. The mechanism of the Cr(VI) removal was mainly chemical reduction.